Analisis Surah Al-Baqarah Ayat 185 dan Surah Al-A’raf Ayat 26 dalam Kajian Al-Istikhdam dan Al-Istithrad - Abdur Rahim; Aulia Unnisa; Salwa Haifa; Harun Al-Rasyid (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study analyzes Surah Al-Baqarah verse 185 and Surah Al-A'raf verse 26 through the lens of balaghah, focusing on the concepts of al-istikhdam and al-istithrad. Istikhdam refers to the use of words with layered or interconnected meanings, while istithrad denotes the inclusion of supplementary explanations that appear tangential to the main theme but remain contextually relevant. The analysis of Surah Al-Baqarah verse 185 highlights the use of istikhdam in conveying meanings related to fasting, divine law, and guidance, encompassing both spiritual and legal dimensions, thereby emphasizing Ramadan as a month of guidance and forgiveness. In Surah Al-A'raf verse 26, istikhdam is evident in the mention of clothing as a symbol of both physical and moral protection, while istithrad elaborates on its connection to piety as a spiritual value transcending material aspects. This study demonstrates how these verses integrate al-istikhdam and al-istithrad to reinforce moral and legal messages while showcasing the linguistic beauty of the Qur'an.